Child poverty: Trends and policy options - Anna Henry; Tom Wernham (Institute for Fiscal Studies (IFS), 2024)
Relative child poverty has increased. Which children are most likely to be affected? What policies would most effectively reduce child poverty?
Keywords: 330; Employment and income; Poverty; inequality and social mobility; Taxes and benefits; Benefits; Labour supply and workforce; Living standards; Poverty; Universal credit; Working age benefits